Hybrid seed production in cauliflower (Brassica oleracea var botrytis subvar cauliflora) - SELVAKUMAR, P; SINHA, S N; PANDITA, V K (The Indian Journal of Agricultural Sciences, 2011)
A study was carried out during 2001-02 and 2002-03 at Kamal, to determine the effect of different sowing dates and planting ratios on hybrid seed yield and quality of cauliflower (Brassica oleracea L. var botrytis L. subvar cauliflora DC). Self incompatibility system was used to produce hybrid seed. Female parent is self compatible and male parent (1-3-18- 19) is self incompatible. There were 3 dates of sowing (20 July, 5 August, and 20 August) and 2 planting ratios (4:2 and 8:2). There was no significant difference among different sowings and planting ratios with regard to fruit set per cent, Seeds/silique and silique length. Seed yieldplot, seed yield plant, brancheslplant and siliquelplant showed significant difference among sowing dates in both years. Significantly higher seed yieldlplot (I 363 g during 2001-02 and 1 090 g during 2002-03) and seed yieldlplant (13.87 g during 2001-02 and 20.59 g during 2002-03) were obtained in 20 July sown crop. Except seed yieldiplant in 200 1-02 no other parameter showed significant difference between planting ratios in both years. Curd diameter reduced as the date of sowing was delayed. Number of days required to reach different phenophases also got reduced in both parental lines as the date of sowing was delayed.